2017
DOI: 10.1111/mms.12444
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐identification matches of humpback whales (Megaptera novaeangliae) from feeding areas in Russian Far East seas and breeding grounds in the North Pacific

Abstract: Humpback whales migrate seasonally from high latitude feeding areas to lower latitude breeding areas for mating and calving. In 2004-2006, a North Pacific basin-wide study called SPLASH was conducted as an international collaboration among various groups of researchers. The Russian Far East consists of multiple high latitude feeding areas and during SPLASH, 102 whales were identified and compared to catalogs from breeding areas. Our goal in this study was to further investigate the migratory destinations of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…This study, along with previous song comparison studies, indicates that populations of humpback whales throughout the North Pacific mix on an ongoing basis, and have done so for as long as we have studied them. Photo-identification matches and satellite tagging clearly indicate the potential for ocean-wide mixing, with individuals on one feeding ground migrating to different winter assembly locations; individuals changing their winter destination year to year - and even one record of multiple crossings of the Pacific from Asia to the North American coast 32–42 . However, to date the import of this mixing has often been minimized, as separate North Pacific ‘stocks’ were designated 29,33,40 .…”
Section: Discussionmentioning
confidence: 99%
“…This study, along with previous song comparison studies, indicates that populations of humpback whales throughout the North Pacific mix on an ongoing basis, and have done so for as long as we have studied them. Photo-identification matches and satellite tagging clearly indicate the potential for ocean-wide mixing, with individuals on one feeding ground migrating to different winter assembly locations; individuals changing their winter destination year to year - and even one record of multiple crossings of the Pacific from Asia to the North American coast 32–42 . However, to date the import of this mixing has often been minimized, as separate North Pacific ‘stocks’ were designated 29,33,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the researchers concluded that these whales must be going to a previously unsampled wintering ground (Baker et al, 2013;Barlow et al, 2011;Calambokidis et al, 2008). This hypothesis was further supported by Titova et al (2018) who found a low overall match rate of individual whales from Russia and the Aleutians to any of the wintering grounds in the North Pacific.…”
Section: Introductionmentioning
confidence: 70%
“…Although it has been demonstrated in previous work based on photo-identification and genetic studies that the Philippines, Okinawa and Ogasawara are winter breeding destinations for humpback whales in the western North Pacific (Baker et al, 2008;Calambokidis et al, 2008;Titova et al, 2018;Witteveen et al, 2009), the SPLASH study postulated the existence of a second unknown breeding population. The SPLASH data indicated that the whales feeding from the Aleutians and Bering Islands were not well represented in any of the wintering grounds surveyed during their study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, satellite tracking has thus demonstrated the connection between Hawaii, the Aleutian Islands, and the Bering Sea with unprecedented detail (see also Kennedy et al 2014), supporting the treatment of the Aleutians and the Bering Sea together for abundance estimation (Wade et al 2016, Wade 2017. Interestingly, results from photo-ID and genetic studies of humpback whales in eastern Russia indicate a high degree of separation between the Commander Islands (at the western end of the Aleutians), the east side of Kamchatka Peninsula, and the Gulf of Anadyr, despite their geographic proximity (Calambokidis et al 2008, Titova et al 2017, Richard et al 2018. However, the satellite tracking data from 1997 and 2018 indicated that whales from Hawaii may visit several of these areas, even within the same feeding season.…”
Section: Satellite Trackingmentioning
confidence: 99%